Automated Residential Demand Response Based on Advanced Metering Infrastructure Network. (24th February 2016) - Seo, Jongkwan; Jin, Ju; Kim, Jin Young; Lee, Jae-Jo
Abstract : Demand response (DR) is a major contributor to grid stabilization during peak times. As the scope and functions of DR increase, DR participation of residential customers has attracted great attention. The main issue of DR design for the residential sector is to build an integrated network for exchange of DR signals between the utility operator and home users who want to participate in DR services at various locations. In this paper, we introduce an automated residential DR model based on advanced metering infrastructure (AMI) network. The internationally recognized standard protocol, known as the open automated demand response version 2.0 (OpenADR 2.0), is applied to realize a fully automated DR (ADR). In order to utilize existing AMI devices as ADR resources, the smart meter is modified while retaining current structure and functions, and various ADR devices are developed based on OpenADR 2.0 protocol. Simulation and demonstration tests are conducted to confirm conformance of the protocol and to verify load variations of home appliances under our ADR model. The developed software programs have obtained an international certification from the OpenADR Alliance.